2014
DOI: 10.3109/14397595.2014.903596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with IgG4-related disease complicated with perivascular lesions

Abstract: Perivascular lesions show wide distribution in patients with IgG4-RD. Serum CRP levels are not necessarily elevated in these patients. Steroid therapy is effective in IgG4-RD and results in resolution of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…[32][33][34][35][36][37][38][39] Lindsay and colleagues presented a case with periaortitis. 32) An abdominal CT scan revealed periaortic soft tissue surrounding the abdominal aorta from below the level of the renal arteries.…”
Section: Aortic Lesionsmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] Lindsay and colleagues presented a case with periaortitis. 32) An abdominal CT scan revealed periaortic soft tissue surrounding the abdominal aorta from below the level of the renal arteries.…”
Section: Aortic Lesionsmentioning
confidence: 99%
“…IgG4-related diseases are newly recognized systemic disorders, and they can affect a variety of different organs. IgG4-related inflammatory changes can also cause different morphological changes in the aorta [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…By using PET-CT and enhanced CT, Ebe et al identified 7 patients (mean age, 70 years; male prevalence, 86%) with IgG4-related perivascular lesions among 21 patients diagnosed with IgG4-related disease by CDC [52]. In their series, aneurysmal dilatation was not observed in any of the patients with enhanced FDG uptake in the perivascular regions.…”
Section: New Diagnostic Methods For Igg4-related Periaortitis/periartmentioning
confidence: 99%